The analysis of absorption capacity of project beneficiaries contributing to cross-border programmes based on the most fundamental criteria - Simó, Balázs (Applied Studies in Agribusiness and Commerce, 2016)
Subsequent to the experience with the international aid programmes of the 1990’s, from the very beginning of the accession negotiations and since 2004 in particular, the notion of absorption capacity of using EU funds has gradually been in focus. The subject of early scientific investigations concentrated mainly on the analysis of the macro-economic conditions of individual countries; furthermore, on increasing absorption capacities as well as how to develop the institutional system of cohesion policy further. After 2004, however, succeeding further rounds of the enlargement as well as after the programming period 2007-2013 in particular – meaning as well the conclusion of the EU budgetary period – the analysis of absorption capacities could be produced at the level of project beneficiaries. The aim of this study is to examine the most prominent determinants influencing successful outcomes and the quality of vigorous projects managed by potent beneficiaries and consortia participating in the European Territorial Co-operation Programmes with the contribution of Hungary. In the course of research correlations between determinants have been subject to econometric analysis revealing the fact that the implementation capacities of state-owned project beneficiaries and those of the non-governmental sector diverge significantly. Moreover, the study aims to show how the institutional system distributing EU funds tends to be rather lax towards the beneficiaries with weak absorption capacities, thus sacrificing the efficiency of developments for pure statistics.JEL code: R58